(3TQM ebOeI RcQjG GdCfUGQj aj GdcdGe Ydi GdHSedIs - (3TgGH GdOjf eMeO CMeO Hf YHO GdMb GdSfHGWj , J (B995 (3g`s; (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdTGaYj , CHh jMji,J (B926 (3g` s
(3ChdgG (B:s
(3hHYO agPG TQM dWja Yi GdebOeI GdJi hQOJ dTjN GdESdGe CHh jMji RcQjG GdCfUGQj GdTGaYj aj GdcdGe s
(3BNQgG (B:s
(3EfgG eNJGQI dg adjJfG hdgG GdENJjGQj daXkG s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B46 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B182 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B374s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs